(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Endodontic treatment is a fundamental dental procedure aimed at preserving natural teeth affected by pulpal and periapical pathologies. Despite significant advancements in diagnostic tools, instrumentation systems, and treatment protocols, errors and complications during endodontic therapy remain prevalent and represent a major cause of treatment failure. This comprehensive scientific article analyzes the types, causes, clinical manifestations, and consequences of errors and complications occurring during various stages of endodontic treatment, including diagnosis, access cavity preparation, working length determination, cleaning and shaping, irrigation, obturation, and post-treatment restoration. Emphasis is placed on iatrogenic factors, anatomical complexities, operator-related variables, and material-related issues. Preventive strategies, modern technological solutions, and evidence-based management approaches are discussed in detail to enhance clinical outcomes and long-term tooth survival.